Overview of Cooperative Learning Strategies in Mathematics Teaching and Learning - Acharya, Nara Hari (Innovative Research Journal, 2023)
This conference paper aims to provide an overview of the potential benefits and challenges associated with implementing cooperative learning strategies in mathematics education. By examining various cooperative learning models and their impact on students' learning outcomes, the paper highlights the importance of collaboration and group work in promoting deeper understanding, higher achievement, and improved attitudes toward mathematics. Traditional instructional methods often rely on individual work and teacher-centered approaches, which may limit students' engagement and development of mathematical reasoning abilities. Cooperative learning, however, emphasizes collaboration, active participation, and peer interaction, creating a supportive and interactive learning environment. This paper reviews the literature on cooperative learning in mathematics education, discusses its benefits, and provides practical recommendations for implementing cooperative learning strategies in mathematics classrooms.